Gambaran Kadar Pb (TIMBAL) dalam Urine pada Pekerja Peleburan Logam di Perkampungan Industri Kecil (PIK) - Luthfi Puspita Sari (Poltekkes Kemenkes Semarang, 2020)
Many lead used in a variety of industrial activity, one of them metal fusion. Lead distill most through inhalation, that comes from particle or vehicle fumes. Lead distill on worker metal fusion at Perkampungan Indutry Kecil (PIK) happened because the worker still incomplete in use self protection. High lead degree in blood, by will heart in detoxification by the kidneys as excretion organ in form of urine. Kidneys can excretion lead through urine the most is approximately 75-80%. The objective research know the level of lead (Pb) in the urine on workers metal fusion at PIK Kebasen Tegal regency. Research Methods an observational study. Nonprobability sampling technique using purposive sampling total 27 sample. The research data served in descriptive the shape of chart to describe level plumbum in urine metal fusion working. The study was conducted on January 29-30, 2020 at PIK Kebasen Tegal regency. Lead levels from 27 samples no metal fusion workers who have plumbum levels exceeding the threshold value of Â <0.01 mg/L.According to research conducted obtained the lead levels in urine on metal fusion workers above the threshold value is <0.01 mg/L